Instilling Children's Ocean Literacy Through Comic Media: STEAM to R-SLAMET Learning Design for ECE educators - Hapidin; Syarah, Erie Siti; Pujianti, Yuli; Gunarti, Winda (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
Ocean literacy is currently at the forefront of the development of the notion of marine environmental sustainability. It is critical to compare ocean literacy ideas in curriculum standards. Comics Convey various messages of maritime insight content on integrated, contextual, and meaningful learning. This study aims to design STEAM (to R-SLAMET; Religion, Science, Literacy, Art, Math, Engineer, and Technology) learning that contains ocean literacy messages in a comic media. Through the qualitative research method with study case type, researchers seek to aid early childhood education (ECE) educators in designing R-SLAMET learning through the media to overcome maritime cultural literacy problems. The participants of this study consisted of three educators and 43 children. The findings show that the natural play experience of early childhood can be a source of inspiration to find ocean literacy through R-SLAMET learning activities. Contextual play by children becomes a reference for designing comic-based R-SLAMET learning. Comic media can integrate R-SLAMET learning in improving children's ocean literacy. Keywords: children ocean literacy, comic media, STEAM to R-SLAMET learning design References: Arthur, J. (1990). Cultural Literacy. College English, 52(3), 281–281. JSTOR. https://doi.org/10.2307/377758 Campbell, D. T., & Stanley, J. C. (2015). Experimental and Quasi-Experimental Designs for Research. Ravenio Books. https://books.google.co.id/books?id=KCTrCgAAQBAJ Castek, E. J., Hagerman, M. S., Woodard, R., Bonine, K., Coiro, J., Graville, C., Jordan, M., Mencher, R., Olivares, M., Smith, B. E., Stornaiuolo, A., Sult, L., Tan, E., Tucker-raymond, E., & Wen, W. (2019). Principles for Equity-centered Design of STEAM Learning-through-Making. 34–35. Chang, C.-C., Hirenkumar, T. C., & Wu, C.-K. (2021). The Concept of Ocean Sustainability in Formal Education—Comparative Ocean Literacy Coverage Analysis of the Educational Standards of India and the USA. Sustainability, 13(8), 4314. https://doi.org/10.3390/su13084314 Chujan, W., Kilenthong, W. T., Patricia, A., Robert, J., Richard, C., Charles, D., John, D., Jere, E., Leslie, A., Jerome, S., Robert, C., Bancroft, K., Lee, J., Carol, S., Lees, N., Mills, R., Haley, S., Eleanor, E., Robert, P., … Erden, F. T. (2019). An early evaluation of a HighScope-based curriculum intervention in rural Thailand. International Journal of Innovation, Creativity and Change, 12(103), 17–25. https://doi.org/10.7822/omuefd.604939 Creswell, J. W. (2015). Educational research: Planning, conducting, and evaluating quantitative and qualitative research (Fifth edition). Pearson. Fortner, R. W., & Mayer, V. J. (1989). Marine and aquatic education – a challenge for science educators. Science Education, 73(2), 135–154. https://doi.org/10.1002/sce.3730730203 Hapidin, Gunarti, W., Pujianti, Y., & Siti Syarah, E. (2020). STEAM to R-SLAMET Modification: An Integrative Thematic Play Based Learning with R-SLAMETS Content in Early Child-hood Education. JPUD - Jurnal Pendidikan Usia Dini, 14(2), 262–274. https://doi.org/10.21009/jpud.142.05 Hapidin, Nurjannah, S. H. (Universitas N. J. (2018). Pengembangan Model Pembelajaran Tematik Seribu. Pendidikan Usia Dini, 12(Marine Education), 51–65. https://doi.org/10.21009/JPUD.121 Hartley, B. L., Thompson, R. C., & Pahl, S. (2015). Marine litter education boosts children’s understanding and self-reported actions. Marine Pollution Bulletin, 90(1), 209–217. https://doi.org/10.1016/j.marpolbul.2014.10.049 Hawthorne, M., & Alabaster, T. (1999). Citizen 2000: Development of a model of environmental citizenship. Global Environmental Change, 9(1), 25–43. https://doi.org/10.1016/S0959-3780(98)00022-3 Hermawanti, O., & Susilaningsih, S. (2020). Development of Educational Comic Media Based on PowerPoint Class III Indonesian Language Content. Elementary School Teacher, 4(2), 5. https://doi.org/10.15294/est.v4i2.29027 Hidayat, S., & Ridwan. (2017). Kebijakan poros maritim dan keamanan nasional indonesia: Tantangan dan harapan. Pertahanan & Bela Negara, 7(3), 107–121. Koutníková, M. (2018). The Application of Comics in Science Education. Acta Educationis Generalis, 7(3), 88–98. https://doi.org/10.1515/atd-2017-0026 Melliou, K., Moutafidou, A., & Bratitsis, T. (2014). Digital Comics Use to Develop Thinking Dispositions in Early Childhood Education. 2014 IEEE 14th International Conference on Advanced Learning Technologies, 502–504. https://doi.org/10.1109/ICALT.2014.148 Mogias, A., Boubonari, T., Realdon, G., Previati, M., Mokos, M., Koulouri, P., & Cheimonopoulou, M. Th. (2019). Evaluating Ocean Literacy of Elementary School Students: Preliminary Results of a Cross-Cultural Study in the Mediterranean Region. Frontiers in Marine Science, 6, 396. https://doi.org/10.3389/fmars.2019.00396 Mokos, M., Realdon, G., & Zubak Čižmek, I. (2020). How to Increase Ocean Literacy for Future Ocean Sustainability? The Influence of Non-Formal Marine Science Education. Sustainability, 12(24). https://doi.org/10.3390/su122410647 Ntobuo, N. E., Arbie, A., & Amali, L. N. (2018). The Development of Gravity Comic Learning Media Based on Gorontalo Culture. Jurnal Pendidikan IPA Indonesia, 7(2), 246–251. https://doi.org/10.15294/jpii.v7i2.14344 Oliver, K. L. (1998). A Journey into Narrative Analysis: A Methodology for Discovering Meanings. Journal of Teaching in Physical Education, 17(2), 244–259. https://doi.org/10.1123/jtpe.17.2.244 Pramitasari, M., Yetti, E., & Hapidin, H. (2018). Pengembangan Media Sliding Book Untuk Pengenalan Sains Kehidupan (Life Science) Kelautan Untuk Anak Usia 6-7 Tahun. JPUD - Jurnal Pendidikan Usia Dini, 12(2), 281–290. https://doi.org/10.21009/jpud.122.09 Puspitorini, R., Prodjosantoso, A. K., Subali, B., & Jumadi, J. (2017). Penggunaan Media Komik Dalam Pembelajaran Ipa Untuk Meningkatkan Motivasi Dan Hasil Belajar Kognitif Dan Afektif. Jurnal Cakrawala Pendidikan, 3(3). https://doi.org/10.21831/cp.v3i3.2385 Rahmatullah, R., Inanna, I., Rakib, M., Mustari, M., & Rabania, R. (2020). Developing Tematic Economic Comic with Characters for Early Childhood. Journal of Educational Science and Technology (EST), 293–300. https://doi.org/10.26858/est.v6i3.14949 Rina, N., Suminar, J. R., Damayani, N. A., & Hafiar, H. (2020). Character education based on digital comic media. International Journal of Interactive Mobile Technologies, 14(3), 107–127. https://doi.org/10.3991/ijim.v14i03.12111 Santoro, F., Santin, S., Gail, S., Fauville, G., & Tuddenham, P. (2017). Ocean Literacy for All; A toolkit. UNESCO United Nations Educational. Steel, B. S., Smith, C., Opsommer, L., Curiel, S., & Warner-Steel, R. (2005). Public ocean literacy in the United States. Ocean & Coastal Management, 48(2), 97–114. https://doi.org/10.1016/j.ocecoaman.2005.01.002 Syarah, E. S., Yetti, E., Fridani, L., Yufiarti, Hapidin, & Pupala, B. (2019). Electronic comics in elementary school science learning for marine conservation. Jurnal Pendidikan IPA Indonesia, 8(4), 500–511. https://doi.org/10.15294/jpii.v8i4.19377 Tatalovic, M. (2009). Science comics as tools for science education and communication: A brief, exploratory study. Journal of Science Communication, 8(4). Tuddenham, P., Schoedinger, S., Cava, F., & Strang, C. (2005). Science Content and Standards for Ocean Literacy: A Report on Ocean Literacy. https://doi.org/10.13140/RG.2.2.12126.84804 Visbeck, M. (2018). Ocean science research is key for a sustainable future. Nature Communications, 9(1), 690. https://doi.org/10.1038/s41467-018-03158-3 Yulianti, D., Khanafiyah, S., & Sulistyorini, S. (2016). Inquiry-Based Science Comic Physics Series Integrated with Character Education. 7. Yunandar, Y. (2018). Budaya Bahari Dam Tradisi Nelayan di Indonesia. Sabda: Jurnal Kajian Kebudayaan, 1(1), 22. https://doi.org/10.14710/sabda.v1i1.13243